2017
DOI: 10.21037/atm.2017.08.10
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of response to immunotherapy—a review from the Spanish Melanoma Group (GEM)

Abstract: Immunotherapy has become a key element in the treatment of several tumors, such as lung carcinoma and melanoma. Immunotherapy, unlike classical chemotherapy and targeted drugs, may yield long-term survival, even in patients who stop treatment due to toxicity. This fact has generated considerable excitement and a real shift in the paradigm of cancer treatment. However, only a small subset of patients benefit from immunotherapy. Survival curves show that most patients have progression of the disease in the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 43 publications
7
17
0
Order By: Relevance
“…Many studies have shown that the infiltration of CD8 + cytotoxic T cells plays key roles in the cancer-initiating cell (CIC) response (20), but the roles and clinical impact of FOXp3 + regulatory T cells on the CIC response are not fully understood (21). A previous report has shown that PD-L1 expression in SM (22,23), and all types of melanoma (24) is associated with CD8 + lymphocytes, consistent with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Many studies have shown that the infiltration of CD8 + cytotoxic T cells plays key roles in the cancer-initiating cell (CIC) response (20), but the roles and clinical impact of FOXp3 + regulatory T cells on the CIC response are not fully understood (21). A previous report has shown that PD-L1 expression in SM (22,23), and all types of melanoma (24) is associated with CD8 + lymphocytes, consistent with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Peripheral blood markers were examined to better characterize the cases in reference to the clinical benefits in immunotherapy. An elevated lactate dehydrogenase (LDH) level was reported to be indicator of tumor burden that is typically associated with lower response rates to immunotherapy, while an elevated platelet-lymphocyte ratio (PLR) was also associated with lower response rates in patients treated with immunotherapy [ 12 ]. The pre-surgery blood exam data were analyzed, which revealed that serum LDH levels were significantly higher in thymomas with mutant GTF2I than those with wildtype GTF2I (thymomas with mutant GTF2I , 224.3 ± 13.3; thymomas with wildtype GTF2I , 183.7 ± 12.1; p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…In line with these results, we found PD-L2 DNA methylation and mRNA expression to be correlated with known prognostic factors, such as tumor-infiltrating lymphocytes and an IFN-γ signature. Tumor-infiltrating lymphocytes are known to be associated with favorable prognosis in primary and advanced melanoma [42,43]. An IFN-γ signature has been shown to be associated with response to immune checkpoint inhibitors [44,45].…”
Section: Discussionmentioning
confidence: 99%